A 3'UTR SNP in NLRP3 gene is associated with susceptibility to HIV-1 infection. - Pontillo, Alessandra; Brandão, Lucas A; Guimarães, Rafael L; Segat, Ludovica; Athanasakis, Emmanouil; Crovella, Sergio (J Acquir Immune Defic Syndr, 2010)
OBJECTIVES: Innate immunity genes polymorphisms are known to be involved in the multifactorial susceptibility to HIV-1 infection. Recently it has been hypothesized that inflammasomes could play an important role in the host response to viruses. The aim of our study is to verify if single-nucleotide polymorphisms (SNPs) in genes encoding for NALPs-innate immune receptors that form molecular complexes leading to the production of IL-1beta and the activation of immune response-could influence the individual susceptibility to HIV-1. DESIGN: We performed an association study analyzing 2 NLRP1 and NLRP3 SNPs in HIV-1 vertically infected Brazilian children (n = 135), HIV-1-infected Brazilain adults (n = 192) and HIV-1-positive Italian seropositive subjects (n = 192). RESULTS: The 3'UTR NLRP3 rs10754558 SNP was associated with HIV-1 infection in all the studied groups. The frequency of rs10754558 G allele was differently distributed within seropositive subjects (HIV+) and controls, and in particular the GG genotype was less frequent in HIV+. CONCLUSIONS: susceptibility to HIV-1 infection is associated with a 3'UTR NLRP3 polymorphism. This is the first report linking SNPs in the NALPs with HIV-1 infection, and further epidemiologic and functional studies are needed to deeper investigate the role of inflammasome in the susceptibility to HIV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Male; Middle Aged; Polymorphism, Single Nucleotide; Pregnancy; Young Adult